ANALISIS PENGARUH NILAI TUKAR, HARGA PENGELUARAN PEMERINTAH, CGDP RELATIF TERHADAP US, DAN CGDP PER PEKERJA TERHADAP PERTUMBUHAN EKONOMI DI EMPAT NEGARA BERKEMBANG ASEAN PERIODE 1970-2010 - Rany, Margareta Putri (University of Surabaya, 2013)
This study intended to identify the effect of exchange rate, the price of government expenditure, CGDP relative to US and CGDP per worker to economic growth in developing countries of ASEAN members. Object used in this study are developing countries of ASEAN founding members with relatively high economic growth.This study are using quantitative approach and pooling data regression method. This research usedÂ samples from four developing countries in ASEAN : Malaysia, Thailand, Philippines and Indonesia in the period 1970 to 2010. The findings of this study indicate that there is a positive and significant impact on the exchange rate, the price of government expenditure, and income per worker on economic growth. While per capita income negatively and significant affect economic growth. These findings support the theory of aggregate demand and supply, which states that the exchange rate, income per capita, and government expenditure to be one of the deciding factors in determining a countrys economic growth.